Penguatan Nilai-Nilai Islam Moderat Melalui Kegiatan Kajian Aswaja Berbasis Digital (Studi Kasus PAC IPNU IPPNU Kecamatan Kedamean) - Moch. Wachidul Qohar; Nur Hudah; Suparno (Jurnal Pendidikan Agama Islam Miazhar, 2023)
Strengthening moderate Islamic values ​​through digital-based aswaja study activities (case studies) PAC IPNU-IPPNU Kedamean District. The research method uses qualitative with a case study approach to find out how planning, implementation, positive impacts, obstacles and solutions relate to the title being researched within the PAC IPNU-IPPNU Kadamean organization. Data collection techniques use observation, interviews and documentation methods. The data analysis techniques used are data reduction, data presentation, and data validity. The results of this research show that the teachings of the Aqidah Ahlussunnah wal Jamaah through social media are certainly very helpful in spreading moderate Islamic values ​​to all students in the Kedamean sub-district, namely by creating da'wah content and publishing information through digital newspapers in run by PENA team.